Development of Good Procurement Information System Web Based at PT. XYZ - Hutajulu, Kristina; Ariyanto, Sisia Dika; Rascalia, Radix (SENATIK STT Adisutjipto, 2019)
PT. XYZ is one of the companies engaged in the production of motorcycle spare parts. In carrying out its operational activities, PT. XYZ has a procurement process. Generally in applying of good procurement, employees must submit a document submission of goods in the printed form and must meet their supervisor directly to ask for approval in a signature. This condition requires quite a long time until the submission document reaches the Director because they have to wait for the signature of each related section. That is quite an obstacle for the employee who submits because the longer the approval process, the longer the procurement process. To overcome this obstacle, a good procurement information system web based was built using phased development methodology. The information system uses SQL Server as database and ASP.Net as programming language. Good procurement information system web-based can accelerate the procurement process.